Al-Kharj during the reign of the first Saudi state (1157-1233 AH / 1744-1818 AD) - Alsaeed, Khalid Abdullah (Journal of Humanities & Social Sciences, 2021)
This study describes the political, economic and scientific conditions of the city of Al-Kharj during the reign of the first Saudi state (1157-1233 AH / 1744-1818 AD). Firstly, on the political level, Al-Kharj is considered one of the most hostile cities in Diriyah for years, and it occurred in many wars, before it submitted. Secondly, on the economic level, Al-Kharj has two advantages that it is less likely to combine with others: the first is that it is an agricultural oasis famous for its abundance of water, fertility of its soil and good harvests, and the second is that it occupies a unique location that made it a passage for pilgrimage and trade caravans. Thirdly, on the scientific level, Al-Kharj, according to the sources and references available to us, witnessed jurisprudential diversity prior to its accession to the Saudi state, but it was not an active scientific center, and perhaps the future reveals to us secrets that we do not know and contradict our understanding.